(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In this research, a study was conducted to determine the axial shortening and axial loading for a total of 30 columns specimens. It consists of six plain control columns, six reinforced columns with a minimum steel content of 0.8 percent of cross section, and eight plain strengthen columns with varying layers of CFRP one, two, and three in the transverse direction for different concrete grades M 20, M 30, and M 40. For the repair and retrofitting of concrete structures, externally bonded fibre reinforced polymer (FRP) composites have become increasingly common. FRP composites are popular because of their well-known benefits, which include a high strength-to-weight ratio and superior corrosion resistance. The use of FRP composites as a confining material for retrofitting existing reinforced concrete (RC) columns with FRP jackets is a common application. The carbon fibre utilised in this investigation is known as Nitowrap and is widely accessible on the market. With the use of epoxy adhesive, the fibres are wrapped around the column. The experimental results reveal that rounded sharp increases load carrying capacity up to two layers of CFRP wrapping in the transverse direction, while ductility rises up to three layers of wrapping as compared to the control. The toughness index of the reinforced column rises as the concrete grade rises, and as the number of CFRP sheet layers rises.